Sintesis Dan Karakterisasi Komposit TiO2-Montmorillonit, Sebagai Fotokatalis Dalam Degradasi Zat Warna Metil Blue - Alam, Muhammad Nur (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
The TiO2-Montmorillonite (Ti-MMT) composite has been synthesized with the aim of increasing the ability of the TiO2 photocatalyst to degrade blue metal. The TiO2-MMT composite was characterized by FT-IR, XRD and SAA. Titanium dioxide is an important material that has been widely researched by experts. TiO2 has unique electronic and optical properties, so it can be used as a catalyst and in various other applications. This compound has been synthesized using various synthesis methods. This article aims to summarize various methods of TiO2 synthesis, morphology, and crystallization of TiO2 with nanostructures. Research is carried out through literature study or literature review. The review results show that TiO2 can be synthesized via various methods, including hydrothermal, solvothermal, sol-gel, direct oxidation, chemical vapor deposition, electrodeposition, sonochemistry, and microwave-based methods. The most commonly found crystal phase is the anatase phase.